Role of roughness geometry function on spatially averaged form induced shear stresses and pressure energy diffusion rates in gravel-bed stream. Issue 3 (3rd July 2022) - Ghosh, Mithun; Malakar, Pritam; Das, Ratul
ABSTRACT: Stream-bed porosity has received substantial interest of research in the field of fluvial hydraulics since few decades and the focus of our present study has been on the respond of gravel-bed porosity on form-induced shear stresses and pressure energy diffusion rates in open channel flows. An inherent parameter called roughness geometry function is introduced to further broaden the aforementioned issues within the frameworks of near-bed turbulent flow characteristics. Laboratory experiments were conducted over three rough beds: (a) uniformly poised gravel bed (b) water-worked bed and (c) uniformly poised sphere bed. The roughness geometry functions of the channel beds are compared to those obtained by water displacement method. An acoustic Doppler velocimeter is used to measure the instantaneous velocity components and double-averaging methodology is applied for data interpretation. Most significantly, the form-induced shear stresses were predicted 30–42% of the double averaged Reynolds shear stresses in case of water-worked bed. The extreme upper limits of the form-induced shear stress distributions in all the three beds corroborated the effects of gravel bed porosity. Furthermore, the negative pressure energy diffusion rates with increasing turbulent production provided additional support offering overwhelming evidence of the effects of gravel bed porosity within the interfacial sub-layer.